Meningkatkan Kemampuan Kognitif Anak Melalui Bermain Kartu Angka Kelompok A - Siti Nurjanah; Nurhaedah Nurhaedah; Rahmatiah Rahmatiah (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
This study aims to find out a picture of children's cognitive abilities in recognizing symbols and concepts of numbers 1-10 before and after being given the treatment of Number Card media and to find out whether there is an influence of Number Card media on the ability to recognize symbols and number concepts of children in group A TK Pembina Al-fadhilah. The subjects in this study were group A in Pembina Al-fadhilah Kindergarten, totaling 16 children. The method used is class action research in 3 cycles. Each cycle consists of four phases; planning, execution, observation, and reflection. Based on the results of the study show that with the card playing method, the number can improve children's cognitive abilities, as evidenced by an increase in assessment from pre-cycle, which is only 33.3%, increased in cycle I to 37.5%, in cycle II 62.5%, and in cycle III 87.5%.